Diseminasi Produk Olahan Jamur Tiram Putih (Pleurotus ostreatus) Dalam Mendukung Program Makanan Bergizi Gratis (MBG) SMA IT Qurrota A’yun Jayapura - Irma Rahayu; Supeni Sufaati; Suharno; Alpredo Dias Agape L. Toruan; Annisa Alfadillah Ruhani; Sherlita Maulani (Jurusan Biologi FMIPA Universitas Cenderawasih, 2025)
The dissemination of processed white oyster mushroom (Pleurotus ostreatus) products in support of the Free Nutritious Food Program (MBG) aims to enhance the knowledge and skills of students at Qurrota A'yun Integrated Islamic Senior High School (SMA IT) Qurrota A'yun Jayapura regarding the importance of consuming nutritious food through the utilization of white oyster mushrooms as a local food ingredient supporting the MBG program. This activity was motivated by the low level of students’ nutritional awareness and the limited variety of nutritious foods available in the school environment. The methods employed included socialization, demonstrations, and hands-on training in processing oyster mushrooms into three healthy food products crispy mushrooms, mushroom nuggets, and mushroom dimsum. The activity involved 20 students from grades X and XI. Evaluation was conducted using pre-test and post-test assessments to measure improvements in participants’ knowledge. The results indicated a significant increase in students’ understanding of the benefits and nutritional value of oyster mushrooms, rising from 55% to 100%. Furthermore, 70% of the participants expressed willingness to try and consume processed oyster mushroom products as an alternative MBG food option. Crispy mushrooms emerged as the most preferred product due to their savory flavor and crispy texture. Overall, this activity successfully enhanced nutritional awareness, developed healthy food processing skills, and created opportunities for the development of oyster mushroom based products as an innovative and sustainable food source to support the MBG program in schools in Jayapura.